2020
DOI: 10.1038/s41598-020-64415-4
|View full text |Cite
|
Sign up to set email alerts
|

Insight into the structural, elastic and electronic properties of a new orthorhombic 6O-SiC polytype

Abstract: Different polytypes of SiC are described and predicted in literature. Here, we report the first occurrence of an orthorhombic 6O-SiC polytype as rock-forming mineral in the nickel laterite mine of Tiebaghi (New Caledonia). This new class of SiC crystallizes in the space group Cmc21 with 12 atoms per unit cell [a = 3.0778(6) Å, b = 5.335(2) Å, c = 15.1219(6) Å, α = 90°, β = 90°, γ = 120°]. The density of 6O-SiC is about 3.22 g/cm3 and the calculated indirect bandgap at room temperature of 3.56 eV is identical t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
8
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 7 publications
(8 citation statements)
references
References 38 publications
0
8
0
Order By: Relevance
“…In the case of 6H-SiC, the experimental characteristic phonon modes are assigned as follow [50]: E 2 (TA) at 151 cm −1 , E 1 (TA) at 240 cm −1 , A 1 (LA) at 504 cm −1 , E 2 (TO) at 762 and 783 cm −1 , E 1 (TO) at 791 cm −1 and A 1 (LO) at 887 and 963 cm −1 , respectively. For SiC in the siliceous breccia, the main Raman peaks were confirmed and matched with Raman-active vibrational modes of orthorhombic SiC structure with Space Group Cmc2 1 [17].…”
Section: Pore Fillings In the Siliceous Brecciamentioning
confidence: 69%
See 3 more Smart Citations
“…In the case of 6H-SiC, the experimental characteristic phonon modes are assigned as follow [50]: E 2 (TA) at 151 cm −1 , E 1 (TA) at 240 cm −1 , A 1 (LA) at 504 cm −1 , E 2 (TO) at 762 and 783 cm −1 , E 1 (TO) at 791 cm −1 and A 1 (LO) at 887 and 963 cm −1 , respectively. For SiC in the siliceous breccia, the main Raman peaks were confirmed and matched with Raman-active vibrational modes of orthorhombic SiC structure with Space Group Cmc2 1 [17].…”
Section: Pore Fillings In the Siliceous Brecciamentioning
confidence: 69%
“…The structure can be described from SiC4 tetrahedra all sharing their neighbour edges. El Mendili et al [17] showed that 6O-SiC results from the 6H-SiC wurtzite to 3C-SiC rock-salt phase transformation as an intermediate state. The 6O-SiC formation requires at least 4 GPa of pressures and high temperatures 2027-2527 °C.…”
Section: Pore Fillings In the Siliceous Brecciamentioning
confidence: 99%
See 2 more Smart Citations
“…SiC is reported to exist as various polytypes [58][59][60] and according to the published literature, SiC has more than 200 polytypes. 59,61 These polytypes have distinct bandgaps and ionisation energies, 3,62 which eventually affects the electrical resistivity of sintered samples.…”
Section: Factors Affecting Electrical Resistivity Of Porous Sic Ceramicsmentioning
confidence: 99%